IMPACT OF TELEVISION ADVERTISING AND CELEBRITY ENDORSEMENTS ON THE PESTER POWER AND BUYER BEHAVIOUR OF CHILDREN IN INDIA - Fulwadhya, Aakrati / A (2009)
Children these days decide everything. They have indirectly become decision makers of the household. From the purchases in the house to what clothes they want to wear. The market at present is of children and the youth. Children are referred to as ‘the king’ in the consumer group. The aim of this dissertation is to understand the factors responsible for this empowerment of children in the consumer sector. How much of an impact do factors like television advertising and celebrity endorsements have on the children of today and to what extent does it affect their buyer behaviour. The influence of these factors lead them to force their parents to purchase products which the parent had no intentions of buying. Thus the rise of ‘pester power’. The focus will be to understand the reasons for the rise of pester power in homes due to television advertising and celebrity endorsements.